2019
DOI: 10.2214/ajr.18.19742
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI Features and Pathologic Outcome of Wedge-Shaped Lesions in the Peripheral Zone on T2-Weighted Images of the Prostate

Abstract: OBJECTIVE. This study investigates the multiparametric MRI (mpMRI) characteristics and pathologic outcome of wedge-shaped lesions observed on T2-weighted images. MATERIALS AND METHODS. Seventy-six patients with histologically confirmed prostate cancer underwent preoperative 3-T MRI before undergoing radical prostatectomy. Two radiologists worked in consensus to mark wedge-shaped regions of hypointensity on T2-weighted images and assess their appearance on apparent diffusion coefficient (ADC) maps (to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…This study used a cutoff of category 4 or greater and it was observed that the sensitivity of PI-RADSv2.1 was lower compared to that of PI-RADSv2.0. A recent investigation that analyzed surgical cases reported the proportion of csPCa (ISUP grade ≥ 2) in wedge-shaped PZ lesions as approximately 30% [ 24 ]. However, since the proportion of csPCa in surgical cases is much higher compared to biopsy cases, the actual proportion of wedge-shaped csPCa may be lower in the scenarios involving biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…This study used a cutoff of category 4 or greater and it was observed that the sensitivity of PI-RADSv2.1 was lower compared to that of PI-RADSv2.0. A recent investigation that analyzed surgical cases reported the proportion of csPCa (ISUP grade ≥ 2) in wedge-shaped PZ lesions as approximately 30% [ 24 ]. However, since the proportion of csPCa in surgical cases is much higher compared to biopsy cases, the actual proportion of wedge-shaped csPCa may be lower in the scenarios involving biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…According to PI‐RADS v2.1, in the TZ a lenticular noncircumscribed nodule is scored as category 4 or 5, whereas a round circumscribed nodule is scored as category 2 or category 1 when encapsulated (ie, when there is a complete T 2 W hypointense rim) 9 . Similarly, using PI‐RADS v2.1 in the PZ, a linear or wedge‐shaped lesion is scored as a category 2 observation 9,115 . However, subjective assessment of shape has been shown to have only a moderate degree of interreader agreement 116 .…”
Section: Quantitative Features That May Improve Subjective Features I...mentioning
confidence: 99%
“…9 Similarly, using PI-RADS v2.1 in the PZ, a linear or wedge-shaped lesion is scored as a category 2 observation. 9,115 However, subjective assessment of shape has been shown to have only a moderate degree of interreader agreement. 116 Krishna et al showed that quantitative shape features of circularity and convexity were accurate to differentiate between transition zone PCa and BPH nodules (Fig.…”
Section: Shape Analysismentioning
confidence: 99%
“…Most MRI studies of suspected cancer can also be identi ed using only T2-weighted MRI and DWI criteria, as can a signi cant proportion of large tumors and PI-RADS 4 lesions, especially those assigned to the PI-RADS 5 category. DCE-MRI can be useful in detecting small cancers that are less prominent or occult on T2-weighted images and DWI, or when DW images are affected by prostheses [9,25]. Local contrast enhancement increases the con dence of the reader and helps inexperienced readers nd MRI-positive scans [26][27][28].…”
Section: Discussionmentioning
confidence: 99%